Association Between Periodontal Disease and Osteoporosis by Gender: A Nationwide Population-Based Cohort Study. Issue 7 (February 2015) - Lin, Tzu-Hsien; Lung, Chia-Chi; Su, Hsun-Pi; Huang, Jing-Yang; Ko, Pei-Chieh; Jan, Shiou-Rung; Sun, Yi-Hua; Nfor, Oswald Ndi; Tu, Hsiao-Pei; Chang, Chin-Shun; Jian, Zhi-Hong; Chiang, Yi-Chen; et al.
Abstract : Abstract: Periodontitis and osteoporosis are primary concerns in public health and clinical management. The aim of this study was to investigate the association between periodontitis and osteoporosis by gender. Data were retrieved from the National Health Insurance Research Database, Taiwan. A diagnosis of periodontitis was defined on the basis of subgingival curettage, periodontal flap operation, and gingivectomy (excluding those with restorative or aesthetic indications). Multiple logistic regression was used for analysis. After adjusting for age, sex, income, and geographical region, there was a significant association between periodontitis and osteoporosis among women (odds ratio: 1.96; 95% confidence interval 1.17–3.26). The association between periodontitis and osteoporosis was significant among women.